Physicochemical and Microbiological Assessment of Sachet Water in Dutse Urban, Nigeria - Amoo, Afeez Oladeji; Asaju , Catherine Iyabode; Garba , Najib; Adeleye , Adeniyi Olarewaju; Amoo , Florence Kemi; Adeniyi , Kamoru Abdulazeez; Amoo , Nureni Babatunde; Gebbe , Habibu Musa (Indonesian Journal of Green Chemistry, 2025)
The rapid increase in population has greatly intensified the requirement for safe and clean drinking water, giving rise to the widespread use of packaged sachet water, commonly known as “pure water” in Nigeria. However, issues concerning improper handling during production, distribution, and storage raise questions regarding possible contamination. This research analyzes the physicochemical and microbiological quality of sachet water in Dutse Metropolis, Nigeria, bears rising concerns over water safety and public health. Thirty (30) sachet water samples from ten popular brands were collected and analyzed for pH, turbidity, electrical conductivity (EC), total dissolved solids (TDS), total hardness, nitrite, chloride, and calcium concentration. All results showed that physicochemical parameters were within the limits set by the World Health Organization (WHO) and National Standard for Drinking Water Quality (NSDWQ). As noted, pH value was between 6.81 and 7.41, while turbidity was under the WHO suggested maximum of 5 NTU. Microbiological examination indicated the complete absence of total coliforms, Escherichia coli, and total bacterial count which shows good purification methods were applied. However, lack of heavy metal analysis poses a risk due to possible pollution from industrial effluents and agricultural runoff. The study still highlights the need for persistent surveillance and peri-regulation to warrant the safety of sachet water, primarily in metropolitan areas where the public water supply is deficient, while region possesses some encouraging findings. The results aim to assist stakeholders in evaluation assessment of sachet water while emphasizing the dire need to safeguard public health and safety.